Persepsi Emosi dalam Iklan HomePod yang Disajikan Melalui Visual Storytelling - Arbi, Hafiz; Sari, Maya Purnama; Triannisa, Selvia Widi (Visualita Jurnal Online Desain Komunikasi Visual, 2023)
Advertising presentations sometimes only show a problem and solution related to the advertised product. The storytelling aspect of advertising becomes an important factor, it can make the audience feel involved and immersed in the story being conveyed, so that the advertising message is easier to deliver and remember by the audience. The use of inappropriate visuals can make advertising less effective in influencing the audience's decision, and may also be irrelevant to the audience. With the presence of emotions that can create a connection with the audience and influence their decision to buy the advertised product or service. Advertising that uses emotions appropriately can be more effective than advertising that only focuses on rational information. The method is applied by analyzing several sources such as advertisements, journals, and books. The aim is to find out the relationship between visual, storytelling, and emotion in advertising. Techniques such as storytelling and visual can enhance the effectiveness of advertising in delivering messages and influencing the emotions of the audience. Emotional perception also affects purchase decisions. Effective advertisements can influence consumer trends or purchasing decisions.